2014
DOI: 10.1016/j.febslet.2013.12.033
|View full text |Cite
|
Sign up to set email alerts
|

The chaperone FdsC for Rhodobacter capsulatus formate dehydrogenase binds the bis‐molybdopterin guanine dinucleotide cofactor

Abstract: Edited by Miguel De la RosaKeywords: Molybdenum cofactor L-cysteine desulfurase Formate dehydrogenase Chaperone bis-MGD a b s t r a c t Molybdoenzymes are complex enzymes in which the molybdenum cofactor (Moco) is deeply buried in the enzyme. Most molybdoenzymes contain a specific chaperone for the insertion of Moco. For the formate dehydrogenase FdsGBA from Rhodobacter capsulatus the two chaperones FdsC and FdsD were identified to be essential for enzyme activity, but are not a subunit of the mature enzyme. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 32 publications
4
46
0
Order By: Relevance
“…As nucleotides are chemical moieties of the Mo-bisPGD structure 14 , it has been hypothesized that EcFdhD could bind and sulphurate the cofactor before its insertion into FDHs 11 . A recent study supports this hypothesis with the copurification of Mo-bisPGD onto FdsC, an FdhD homologue from Rhodobacter capsulatus 15 .…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…As nucleotides are chemical moieties of the Mo-bisPGD structure 14 , it has been hypothesized that EcFdhD could bind and sulphurate the cofactor before its insertion into FDHs 11 . A recent study supports this hypothesis with the copurification of Mo-bisPGD onto FdsC, an FdhD homologue from Rhodobacter capsulatus 15 .…”
mentioning
confidence: 63%
“…It is noteworthy that this archaeon appears to lack a cysteine desulphurases 18 , which raise the possibility that the FdhD homologue functions as a chaperone only and does not participate in the sulphuration of Mo-bisPGD. In the case of the R. capsulatus FdsC, the sequence harbours two cysteine residues within the loop, but their substitutions for alanine residues did not impair R. capsulatus FDH activity in E. coli 15 . FdsC was shown to bind Mo-bisPGD, consistent with conservation of the residues involved in Mo-bisPGD binding identified in our study.…”
Section: Discussionmentioning
confidence: 93%
“…The terminal electron acceptor for formate oxidation is specifically NAD + (NADP + is not used), which accepts the two electrons from the FMN cofactor. Since in the absence of the chaperones FdsC and FdsD during expression, a heterotrimeric enzyme lacking Moco but containing the set of [FeS] clusters and FMN is formed, it is believed that bis-MGD is inserted into the enzyme after the insertion of the other cofactors into the heterotrimer [113]. So far, the FeS clusters have not been further characterized in R. capsulatus FDH and nothing is known about the proteins that specifically insert the FeS clusters or FMN into FdsGBA.…”
Section: Fes Cluster Containing Molybdoenzymes In Bacteriamentioning
confidence: 99%
“…Recently, it was shown that these chaperones not only facilitate the insertion of bis-MGD into the target enzyme, but also directly bind bis-MGD [88]. This was shown by the FdsC-FdsA system for maturation of R. capsulatus formate dehydrogenase (FDH).…”
Section: Molecular Chaperones For Bis-mgd Insertion Into Targetmentioning
confidence: 99%
“…While FdsD has only counterparts in some oxygen-tolerant FDHs, FdsC shares high amino acid sequence homologies to E. coli FdhD, the chaperone for the membrane-bound FDH (FdhF) [84]. FdsC was directly copurified with bound bis-MGD [88]. The definitive proof that bis-MGD was bound to FsdC and not only MGD was given by the reconstitution of E. coli TMAO reductase activity in a system solely consisting of FdsC and apo-TMAO reductase.…”
Section: Molecular Chaperones For Bis-mgd Insertion Into Targetmentioning
confidence: 99%